Assessing the progress of New American Schools : a status report - Berends, Mark, 1962- (RAND, 1999)
New American Schools (NAS), a private nonprofit corporation, began in 1991 to fund the development of designs aimed at transforming entire schools at the elementary and secondary levels, seeking to engage the nation's best educators, business people, and researchers in an effort to create, test, and foster the implementation of schoolwide designs that "break the mold." The competition, development, and demonstration phases of this effort have been completed; the current "scaling-up" phase, with the goal of forming a critical mass of schools within partnering school districts, began in 1995. This report describes RAND's plan for collecting the data needed to address the overall questions posed for the effort: What were the NAS schools like before they implemented the designs? How have the designs and the assistance they provide evolved over time? Are the critical components of the NAS designs being implemented across a wide array of schools? Do the NAS designs extend beyond changes in school organization and governance and permeate classrooms to change curriculum and instruction? Over time, what is the progress of the schools being assisted by NAS design teams in improving student and school performance? Also described is RAND's analysis of the baseline characteristics--demographics, climate, and test scores--of NAS schools in the early implementation stages of the scale-up phase, an analysis that sought to answer the first of the overall questions: What were the NAS schools like before they implemented the designs?